Infected empires : decolonizing zombies - Saldarriaga, Patricia; Manini, Emy, 1968- (Global Media and Race Ser., 2022)
"Given the current moment--polarized populations, increasing climate fears, and decline of supranational institutions in favor of a rising tide of nationalisms-- it is easy to understand the proliferation of apocalyptic and dystopian elements in popular culture. Infected Empires examines one of the most popular figures in contemporary apocalyptic film: the zombie. This harbinger of apocalypse reveals bloody truths about the human condition, the wounds of history, and methods of contending with them. Infected Empires considers parallels in the zombie genre to historical and current events on different political, theological and philosophical levels, and proposes that the zombie can be read as a figure of decolonization and an allegory of resistance to oppressive structures that racialize, marginalize, disable, and dispose of bodies. Studying films from around the world, including Latin America, Asia, Africa, the US, and Europe, Infected Empires presents a vision of a global zombie that points toward a posthuman and feminist future"--